Еnvironmental and Legal Regulation of Digitalization of Environmental Protection - BEKEZHANOV, Dauren; KOPBASSAROVA, Gulnurа; RZABAY, Aktoty; KOZHANTAYEVA, Zhaukhar; NESSIPBAYEVA, Indira; AKTYMBAYEV, Kanat (Journal of Environmental Management and Tourism, 2021)
The article is devoted to certain issues of environmental and legal aspects of the digital environment in the information system of environmental safety, issues of legal implementation of the digitalization program. This article has researched the importance and necessity of environmental digitalization. At the same time, the main idea of digital ecology is considered as the implementation of the National Strategy for Sustainable Development and prevention of Environmental Disasters, control of public opinion on environmental issues, improvement of health and increase in life expectancy of the population, adaptation of the state system of digitalization management in the field of environmental culture, environmental education, environmental safety to the digital environment, use of the possibilities of modern "breakthrough" digital technologies. Environmental digitalization in management comprehensive studies of the system approach to the use of digital environmental resources were conducted, the basics of improving the regulatory legal regulation in the management in the field of environmental safety in the framework of the implementation of the digital program were considered .